2012
DOI: 10.1038/ng.2324
|View full text |Cite
|
Sign up to set email alerts
|

Dominant missense mutations in ABCC9 cause Cantú syndrome

Abstract: Cantú syndrome is characterized by congenital hypertrichosis, distinctive facial features, osteochondrodysplasia and cardiac defects. By using family-based exome sequencing, we identified a de novo mutation in ABCC9. Subsequently, we discovered novel dominant missense mutations in ABCC9 in 14 of the 16 individuals with Cantú syndrome examined. The ABCC9 protein is part of an ATP-dependent potassium (K(ATP)) channel that couples the metabolic state of a cell with its electrical activity. All mutations altered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
248
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(265 citation statements)
references
References 28 publications
13
248
0
4
Order By: Relevance
“…Trio-based whole-exome sequencing was performed on patient 1 and parents as described previously 5 with the alterations that sequencing was performed on the Solid 5500 platform and enrichment was performed using the Agilent Sureselect kit (v4; Agilent, Santa Clara, CA, USA). The obtained average coverage was 69, 77 and 66 Â for the patient, father and mother, respectively.…”
Section: Whole-exome Sequencing and Array Cgh Analysismentioning
confidence: 99%
“…Trio-based whole-exome sequencing was performed on patient 1 and parents as described previously 5 with the alterations that sequencing was performed on the Solid 5500 platform and enrichment was performed using the Agilent Sureselect kit (v4; Agilent, Santa Clara, CA, USA). The obtained average coverage was 69, 77 and 66 Â for the patient, father and mother, respectively.…”
Section: Whole-exome Sequencing and Array Cgh Analysismentioning
confidence: 99%
“…Individuals affected by Cantú syndrome also tend to exhibit coarse facies, similar to acromegaly in appearance. The genetic basis of Cantú syndrome was elucidated by Van bon et al and Harkalova et al in 2012, who demonstrated that mutations in the ABCC9 gene appear to be causative of Cantú syndrome [2,3]. The ABCC9 gene encodes the channel regulation protein SUR2, which acts as part of an adenosine triphosphate-sensitive potassium channel.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the KCNJ11 gene can cause T2DM because of the reduced ability of ATP to inhibit the activity of the KATP channel and the enhanced ability of MgATP to simultaneously stimulate the function of this channel. This is associated with defective insulin secretion, ultimately causing T2DM 28,93 .…”
Section: Role Of Kir62 In Insulin Secretionmentioning
confidence: 99%
“…Both proteins form compartments in the KATP channels which allow potassium to flow into the cell rather than out of it, as mediated by G proteins 28 . The KATP channel interacts with different types of VSCCs, including L (long-lasting), N (neural), P/Q (purkinje), R (residual) and T (transient).…”
Section: Interaction Of Kcnj11 Gene With Other Genesmentioning
confidence: 99%